Pengaruh Brand Image, Price Perception, Fitur, Dan Product Quality Terhadap Keputusan Pembelian Smartphone Xiomi (Studi Pada Mahasiswa Universitas Islam Malang) - Ahmad, Ryan Fazrin; Arifin, Rois; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In the economic realm, business refers to an entity or organization that sells goods and services to consumers or other entities. It is important for companies to understand consumer behavior because the continuity and success of companies, which strive to meet consumer needs and desires, is very dependent on a deep understanding of consumer behavior (Tjiptono F, 2008: 96). In the current digital era, smartphones have become an integral element in people's daily lives. Its function is not only limited as a communication tool, but also as a learning tool, as a tool for accessing information, and carrying out various other activities that can make human life easier. In this way, it is not surprising that the smartphone market is growing and competition between smartphone brands is getting tighter. Xiomi smartphones have become one of the most popular brands in Indonesia in recent years. This is due to the good quality of the product and the price which is relatively more affordable compared to other similar brands. Keywords: Brand Image, Price Perceotionn, Features and Product Quality and Purchasing Decision.